Institutional priorities and budgeting strategies affecting the collecting development of the UPLB Libraries - Maglinao, Erlinda L. (1996)
This study looks into the institutional priorities of the seven colleges of the University of the Philippines Los Baños (UPLB), the budgeting practices employed by their libraries, and which of these priorities and practices affect their collection development programs. The data were obtained using interviews with the seven college deans and twelve librarians-in-charge.